A Fast Iterative Approach for Optimal Control of Nonlinear Systems. Issue 2 (2020) - Liu, Jiaqi; Dong, Shiying; Hong, Jinlong; Gao, Bingzhao; Chen, Hong
Abstract: To improve computational efficiency, a fast iterative solution method is proposed to solve optimization problems of nonlinear systems in this paper. The main idea is to extract the main linear part from the nonlinear system, and then regard the remaining nonlinear part as disturbance, so that the converted system can be solved by combining the optimal solution of the linear system with the fast iterative solution proposed. After the fast iterative solution method is introduced, its effectiveness is validated through a numerical example and an application which is engine energy-saving control while taking vehicle speed tracking into consideration. All of the simulation results show that the proposed iterative algorithm has the advantages of fast convergence speed and high accuracy.